Slow releasing sulphide donor GYY4137 protects mice against ventilator-induced lung injury - Veskemaa, Lilly; Taher, Mahdi; Graw, Jan Adriaan; Gonzalez-Lopez, Adrian; Francis, Roland (Intensive Care Medicine Experimental, 2025)
Background: Cyclic stretching of the lung during mechanical ventilation induces inflammation that contributes to the development of ventilator induced lung injury. Hydrogen sulphide (H2S) is an endogenous gasotransmitter known for its anti-inflammatory properties. However, the administration of exogenous H2S is constrained by its narrow therapeutic window, rapidly leading to potentially toxic peak concentrations. Alternatively, slow-release sulphide donors, such as GYY4137, offer a more controlled delivery. The primary aim of this study is to assess the efficacy and safety of GYY4137 in mitigating VILI. Methods: Anaesthetised male C57BL/6 J mice were pretreated with an intraperitoneal injection of GYY4137 (50 mg/kg, n = 14) or an equivalent volume of phosphate-buffered saline (controls, n = 13) and were then subjected to high tidal volume ventilation (VT 40–42.5 ml/kg) for a maximum of 4 h. Results: GYY4137 pretreatment led to a notable 50% increase in survival rates compared to controls (p = 0.0025). It also improved arterial oxygenation after high VT ventilation, with arterial partial pressure of oxygen (PaO2) of 64 mmHg (IQR 49–125 mmHg) vs. 44 mmHg (IQR 42–51 mmHg) in controls (p < 0.001). Additionally, GYY4137 reduced total protein concentration in bronchoalveolar lavage fluid by 30% (p = 0.024) and lowered IL-1β levels by 40% (p = 0.006). GYY4137 mitigated the decline in dynamic respiratory system compliance caused by high VT ventilation, showing values of 24 μl/cmH2O (IQR 22–27) compared to 22 μl/cmH2O (IQR 22–24) in controls (p = 0.017). GYY4137 had minimal effects on antioxidant gene expression related to the erythroid nuclear factor 2, and it did not affect glutathione metabolism, the nuclear factor kappa B pathway, or the endoplasmic reticulum stress response. Conclusions: In this mouse model of VILI, pretreatment with GYY4137 showed protective effects. GYY4137 significantly improved survival. It also improved arterial blood oxygenation and dynamic respiratory system compliance, and mitigated the development of lung oedema and inflammation.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Biotrauma; Hydrogen sulphide; Sulphide donors; Ventilator-induced lung injury